Simvastatin, dosage and delivery system for supporting bone regeneration, an update review. Issue 3 (May 2016) - Kheirallah, Mouetaz; Almeshaly, Hassan
Abstract: Objective: The purpose of this review is to discuss the dosage, duration and carrier for simvastatin, and to summarize effects of topical application directly or indirectly for stimulating bone regeneration. Methods: We have searched in Pubmed using keywords, simvastatin, dose response, bone regeneration, controlled-release delivery system. This search was complemented with a manual search of the relevant articles cited among the selected papers. The search was among the articles written in English and published in the last 10 years. The articles were revised in depth, and summarized. Results: High dose of simvastatin increases bone formation and resorption, while low dose of simvastatin decreases bone formation and increases bone resorption, furthermore it is reported that high dose of systemic administration of simvastatin will raise the risk of liver failure, kidney disease, and other side effects. Local administration can bypass hepatic degradation of statins to achieve therapeutic concentrations in bone and avoid the systemic side effects. The choice of appropriate carrier will depend on the release kinetics determined to be the best for osteogenesis. Conclusion: Local delivery of simvastatin from carriers appears to be an attractive solution to the problem of maintaining therapeutic doses to treat severe bone defects and to minimize the undesired side effects. Locally delivered simvastatin can increase the bone formation and accelerate healing process of bony defect. Another advantage of local delivery system is that it can stimulate new bone formation in a dose-dependent manner. Further evidence-based studies will be required to determine local delivery concentrations to promote bone regeneration.